Ekspor Gerbong Kereta sebagai Instrumen Diplomasi Ekonomi Indonesia di Asia Selatan - Radithya Rahim Basmala; Muthi Najwa Hanifa; Semeion El Sozo (Department of International Relations, Brawijaya University, 2025)
This study examines the role of PT INKA's export of railway coaches to Bangladesh as an instrument of Indonesia's economic diplomacy to strengthen bilateral cooperation and transportation infrastructure development. PT INKA’s success in entering the Bangladeshi market is supported by product quality, competitive pricing, and technical adaptation to local needs. Indonesia’s economic diplomacy is manifested through multi-actor synergy involving ministries, financing institutions, and industry players in strategic coordination. The findings indicate that this export not only enhances national industry competitiveness but also deepens Indonesia–Bangladesh bilateral relations politically and economically. Global competition and geopolitical dynamics pose challenges that require adaptive diplomatic strategies moving forward. This study highlights the importance of economic diplomacy as a tool to integrate national interests with international cooperation in non-traditional markets.